Subchronic toxicity of the pulmonary hypertension model due to low-dose monocrotaline in rats - Vicente Benavides-Cordoba; Melissa Silva-Medina; María Ximena Varela; Mauricio Palacios Gómez (GarVal Editorial Ltda., 2020)
Context: The study of pulmonary hypertension is mainly based on an experimental model that induces this condition using monocrotaline. Even though this model has been in use for decades, the toxic effect of low dose monocrotaline in other systems is not well described. Aims: To evaluate the renal and hepatic effects of monocrotaline in order to be able to better predict the pharmacodynamic impact that it could have. Methods: Two groups of rats were used, the first one received monocrotaline following pulmonary hypertension protocol (30 mg/kg) and the second one received saline 0.9%. At day 60 blood from the vena cava was obtained and liver and kidney were extracted for histologic exam. Fulton index (right ventricle hypertrophy measurement) was used to confirm pulmonary hypertension. Results: The monocrotaline group presents focal interstitial lymphoid infiltration and regeneration foci in the kidney as well as venous congestion of the liver in some of the animals, these changes were not found in the control group. Kidney and liver function tests showed no significant differences. These results show that low-dose monocrotaline model for pulmonary hypertension generates changes on liver and kidney; however, these alterations were not consistent, making it a viable model for evaluating new drugs in this condition. Conclusions: The present study demonstrates that the low dose of monocrotaline (30 mg/kg) in animals exposed for 60 days does not cause consistent changes in liver and kidney; there were findings in some animals that could be caused by cardiovascular changes generated by pulmonary hypertension.